Analysis of fraud hexagon theory in detecting fraudulent financial statements: The role of Big 4 - Eska Setia Kuncara; Putra Pamungkas (Universitas Sebelas Maret, 2024)
This study aims to analyze the application of the Fraud Hexagon Theory in detecting fraud in financial statements by considering the role of the Big 4 Public Accounting Firm. This study focuses on research on financial sector companies and banks in Indonesia. The background of this problem begins with the frequent occurrence of financial statement fraud cases, which in turn can harm shareholders and reduce public confidence in the integrity of financial statements. This trend raises the most important question regarding the effectiveness of the Big 4 (Kantor Akuntan Publik-KAP) audits. The research method used is quantitative research, using a secondary data analysis approach based on the company's financial statements. The research sample was selected based on the purposive sampling technique, and the data analysis testing tool used panel data regression analysis with E-Views application to test the hypothesis using various tests needed to form a good regression model. The results of this study indicate that the average fraud on financial statements in the sample taken is relatively low. The findings show that rationalization, ability, and collusion can be used to detect financial statement fraud, while KAP Big 4 can moderate the fraud risk. This study provides new insights into the dynamics of financial statement fraud in Indonesia, especially in the financial and banking sectors, and suggests the need for tighter supervision and improved audit quality to reduce the potential for financial statement fraud.